Pengembangan Media Pembelajaran Smart Box Pada Mata Pelajaran Pendidikan Pancasila Di Kelas Rendah SD Negeri Lidah Wetan II/462 - Ramadhani, Novia Putri; Nazilah, Risma Hidayatu; Devi, Jesica Rahmawati; Salsabila, Ihda; Susanti, Susi; Sukardi, Agustina Trianita Nency; Istiq’faroh, Nurul; Zahroh, Ulfi Aminatuz (CV. Kurnia Grup, 2025)
This study aims to develop and test the effectiveness of learning media “Smart Box Rules at Home and at School” in helping students understand the material in learning Pancasila Education in Elementary School. Media “Smart Box Rules at Home and at School” is a learning media in which there is material and interactive games that can help students understand the concept of material. This research uses the Reasearch and Development (R&D) method with the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluate). The research instruments used were student and teacher interview guidelines. The data taken is the need for “Smart Box” media development, the feasibility of “Smart Box” media, and students' responses regarding the feasibility of “Smart Box” media. The results showed that teachers and students gave positive responses to the use of “Smart Box” media. It can be seen in the results of the “Smart Box” product validation assessment from material and media experts who obtained an average presentation of 100% with very good or feasible criteria. Through the interview guidelines for students after using the “Smart Box” media, it can be seen that students give very good responses and responses by obtaining an average percentage of 100%. Based on the results of the study, it can be concluded that the media “Smart Box” “Rules at Home and at School” is effective and feasible to use in helping students to learn.